SISTEM SERTIFIKAT DIGITAL (SSD) DENGAN METODE WATERMARKING BERBASIS CLOUD COMPUTING: INDUSTRIAL REVOLUTION, INTEGRATION, AUTHENTICATION, MANDIRI, DIGITAL DOCUMENTS. - Puad, Lailyn; Limia Budiarti, Rike (LP2M STMIK Nurdin Hamzah Jambi, 2019)
University and industry became the sectors most demanded for change with the development of the Industrial Revolution 4.0 issue. One of the basic things is about security, data integration and reducing paper usage. This system can be used as one of the answers to some of these demands, with the ability to produce digital documents integrated with one account. In addition, the authenticity of documents is guaranteed, with the standalone authentication feature owned by the application, so that not everyone can duplicate it. Utilizing the Qrcode that is integrated with the Codeigniter framework can produce an application that is able to provide convenience to each of its users in a variety of things, from organizing digital documents with adequate security guarantees, reducing paper usage to integrating affordable data.